Matematika v predšolskem obdobju - Lipovec, Alenka; Antolin Drešar, Darja (2019)
Mathematics in Preschool. Early attention to the important skills of the 21st century is the commitment of every modern society. Mathematical competence is one of the key competencies and the level of achievement of this competence is closely linked to the development of society. Therefore, it is necessary to create conditions for the development of mathematical thinking very early. The textbook Mathematics in Preschool is intended for future preschool teachers. We are hoping that the textbook will help them to structure and deepen the knowledge that we develop in mathematical courses at the study program Preschool education at the University of Maribor, Faculty of Education. Certain parts of the text, especially the activities, might also be helpful for parents who would like to perform mathematical but fun activities with children. As well, the textbook is warmly recommended to all those interested in teaching early mathematics. The textbook is divided into chapters and subchapters. Each content section begins with a theoretical part, in which we also get acquainted with some of the new concepts. The following are suggestions for different methodical pathways in developing the mathematical knowledge of a preschool child. Activities are marked in a special way in order to find them in the activity index. At the end of the chapters, we find the keywords. Their definitions are provided in the Glossary section that is in front of the References. The following are questions that help the reader in structuring the knowledge.
Keywords: mathematics; preschool; learning; exercises; games